Emergence of garden spurge (Euphorbia hirta) and large crabgrass (Digitaria sanguinalis) in response to different physical properties and depths of common mulch materials. (9th April 2020) - Saha, Debalina; Marble, S. Christopher; Pearson, Brian; Pérez, Héctor; MacDonald, Gregory; Odero, Dennis
Abstract: Greenhouse and outdoor container experiments were conducted to determine garden spurge and large crabgrass emergence when seeds were placed either on top of or below three different mulch materials [pine bark (PB), hardwood (HW), or pine straw (PS)] applied at five depths (0, 1.3, 2.5, 5.1, and 10.2 cm). To elucidate mulch characteristics that contributed to weed control, photosynthetic active radiation (PAR) was recorded underneath each mulch layer, moisture retention was monitored for 24 h following irrigation, and particle size was determined using standard soil sieves. HW reduced PAR (97%) more than did PB (90%) or PS (92%) at 1.3 cm, but few or no differences were noted between mulches at greater mulch depths. HW also contained the highest percentage of small particles and consequently retained more water (29%), than PB (14%) or PS (22%) 24 h following a simulated irrigation event. Emergence of large crabgrass and garden spurge was consistently greater when seeds were placed on top of the mulch, compared to seeds placed below. Emergence of both species also tended to respond to increasing depth in a quadratic manner, indicating that once a critical level of mulch was applied (2.5 to 5 cm), further reductions in weed emergence would not be observed, at least over the short term (12 wk). PB and PS tended to provide a greater reduction in emergence of both species compared to HW. This research also indicates that larger particle materials such as PB or PS would be advantageous because of their ability to suppress weed emergence regardless of seed position.